Interactions between the inositol 1,4,5-trisphosphate and cyclic amp signaling pathways regulate larval molting in Drosophila. - Venkatesh, K.; Siddhartha, G.; Joshi, R.; Patel, S.; Hasan, G. (Genetics, 2001)
Larval molting in Drosophila, as in other insects, is initiated by the coordinated release of the steroid hormone ecdysone, in response to neural signals, at precise stages during development. In this study we have analyzed, using genetic and molecular methods, the roles played by two major signaling pathways in the regulation of larval molting in Drosophila. Previous studies have shown that mutants for the inositol 1,4,5-trisphosphate receptor gene (itpr) are larval lethals. In addition they exhibit delays in molting that can be rescued by exogenous feeding of 20-hydroxyecdysone. Here we show that mutants for adenylate cyclase (rut) synergize, during larval molting, with itpr mutant alleles, indicating that both cAMP and InsP(3) signaling pathways function in this process. The two pathways act in parallel to affect molting, as judged by phenotypes obtained through expression of dominant negative and dominant active forms of protein kinase A (PKA) in tissues that normally express the InsP(3) receptor. Furthermore, our studies predict the existence of feedback inhibition through protein kinase A on the InsP(3) receptor by increased levels of 20-hydroxyecdysone.